PREFERENSI MAHASISWA TERHADAP PENGAMBILAN KREDIT - Lestari, Anita; Hatimatunnisani, Hani; Meilani, Alya Sheila; Sholih, Dede; Fauzany, Riffka (Jurnal Sosio dan Humaniora (SOMA), 2025)
This study aims to determine students' preferences in credit-taking decisions, as well as to explore the main reasons behind these decisions. This study uses a descriptive quantitative approach, with data collected through an online questionnaire distributed to 50 students at a private university in Bandung. The results of the study showed that most students had never taken credit. The main inhibiting factors were concerns about repayment ability, limited knowledge of credit procedures and provisions, and apprehension about high interest rates. Although many students consider that access to credit services, especially through digital platforms, is quite easy, the results of the study show that their understanding of finance is still limited. Therefore, a more systematic and in-depth financial literacy program is needed so that students can manage financial decisions, especially in terms of credit, wisely and responsibly.